1992
DOI: 10.1007/bf02245147
|View full text |Cite
|
Sign up to set email alerts
|

Preexposure to amphetamine and nicotine predisposes rats to self-administer a low dose of cocaine

Abstract: The acquisition of low-dose (0.25 mg/kg/infusion) intravenous cocaine self-administration was measured in rats that had received nine daily injections of amphetamine (1.0 mg/kg, IP), nicotine (0.6 mg/kg base weight, SC) or vehicle. For control rats, the acquisition of self-administration was gradual with the number of responses per 2 h daily test session increasing between days 3 and 9. By comparison, rats preexposed with amphetamine and nicotine demonstrated elevated response means during the early days of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
149
2
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(187 citation statements)
references
References 26 publications
31
149
2
3
Order By: Relevance
“…Animal studies clearly show that pre-exposure to psychomotor stimulants enhances subsequent SA of such drugs (Horger et al 1990(Horger et al , 1991(Horger et al , 1992Pierre and Vezina 1997;Vezina et al 1999;Lorrain et al 2000). Consistent with pre-exposure to nicotine (Horger et al 1992), and low-dose exposure to amphetamine (Pierre and Vezina 1997) we found a differential effect of low-dose MP preexposure on the reinforcing and locomotor activating effects of cocaine.…”
Section: Adolescent Exposure To Mp Enhances Cocaine Self-administratisupporting
confidence: 80%
See 2 more Smart Citations
“…Animal studies clearly show that pre-exposure to psychomotor stimulants enhances subsequent SA of such drugs (Horger et al 1990(Horger et al , 1991(Horger et al , 1992Pierre and Vezina 1997;Vezina et al 1999;Lorrain et al 2000). Consistent with pre-exposure to nicotine (Horger et al 1992), and low-dose exposure to amphetamine (Pierre and Vezina 1997) we found a differential effect of low-dose MP preexposure on the reinforcing and locomotor activating effects of cocaine.…”
Section: Adolescent Exposure To Mp Enhances Cocaine Self-administratisupporting
confidence: 80%
“…Animal studies have also shown that repeated exposure to psychostimulants increases the likelihood that rats will acquire drug self-administration (SA) with shorter latencies (Horger et al 1992) and at lower doses (Horger et al 1990), perhaps a more relevant display of sensitization as it relates to addiction. Pretreatment with such stimulants as nicotine, caffeine, and amphetamine produces enduring enhancements in the acquisition of cocaine SA (Valdez and Schenk 1994;Schenk and Davidson 1998).…”
Section: Treatment Of Attention Deficit Hyperactivity Disorder With Tmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, self-administration of cocaine produces sensitization to the locomotor-activating effects (Hooks et al, 1994;Phillips and Di Ciano, 1996;Zapata et al, 2003;Ben-Shahar et al, 2004). It has also been demonstrated that rats receiving experimenter-administered stimulants, which produces a sensitized locomotor response, acquire selfadministration faster and/or at lower doses (Horger et al, 1990(Horger et al, , 1992Schenk et al, 1991). Animals treated this way also respond to higher breakpoints when subsequently tested on a PR schedule (Mendrek et al, 1998;Lorrain et al, 2000;Covington and Miczek, 2001;Suto et al, 2002Suto et al, , 2003Vezina et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This period of life is a very sensitive age in which the negative affective state associated with nicotine withdrawal is reduced while the rewarding action of nicotine is enhanced compared to adults (Carcoba et al, 2014;Dickson et al, 2014;Dickson et al, 2011;Hutchison and Riley, 2008;Lee et al, 2015;McQuown et al, 2009;Natividad et al, 2012;Natividad et al, 2010;Natividad et al, 2013;O'Dell et al, 2004;O'Dell et al, 2006;O'Dell et al, 2007;Shram et al, 2008;Torres et al, 2008;Wilmouth and Spear, 2004), making adolescents a vulnerable target to nicotine use and abuse as well as for use of other addictive drugs during adulthood. Consistent with this notion, previous studies have shown that nicotine exposure during adolescence can prime the use and abuse of cocaine, alcohol, and other addictive substances (Bechtholt and Mark, 2002;DiFranza and Guerrera, 1990;Horger et al, 1992;Hutchison and Riley, 2008;Kandel and Kandel, 2015;Kandel and Kandel, 2014;Kelley and Rowan, 2004;Kouri et al, 2001;Levine et al, 2011;Li et al, 2014;McQuown et al, 2007;McQuown et al, 2009;Meliska et al, 1995;Natividad et al, 2010;Rinker et al, 2011;Rosenberg, 2014;Schindler et al, 2012;Schneider et al, 2012). There is also evidence showing that about 90% of regular smokers start using tobacco at an early age, and that early onset smoking carries a major risk for the development of addiction to other drugs of abuse (Rimm et al, 1995).…”
Section: Introductionmentioning
confidence: 78%